Imagining a net-zero Teesside: actors, networks, and expectations in industrial decarbonisation megaprojects - Kyle S Herman; Marfuga Iskandarova; Benjamin K Sovacool (Environmental Research Communications)
Decarbonising industrial clusters is critical to achieving the UK’s net-zero industrial strategy. This study focuses on Teesside, an industrial cluster in Northeast England, analysing its transition through the framework of the Sociology of Expectations (SoE). The research investigates the role of public and private stakeholders in driving decarbonisation efforts, concentrating on a limited set of technologies and large-scale megaprojects, especially carbon capture, hydrogen production, CO _2 and hydrogen transport. The study highlights the challenges of deploying these first-of-a-kind technologies, which are not yet commercially viable in the UK. Our analysis identifies both opportunities and significant risks in Teesside’s approach, particularly the potential over-reliance on a narrow range of technologies. The findings raise concerns about the assumed reductions in costs and carbon emissions, questioning the feasibility of scaling these technologies for long-term industrial sustainability. The main implication is that, should the technologies currently favoured by incumbent industry fail to perform, the expectations could play a double and contradictory role in net-zero transitions—by both motivating actors to legitimise decarbonisation technologies, yet blinding others to the significant challenges that lie ahead.